Pendekatan Maqashid Al-Syari’ah sebagai Pisau Analisis dalam Penelitian Hukum Islam - Pujangga Candrawijayaning Fajri (Jurnal Penelitian Agama, 2022)
The continuous development of the times has resulted in many legal problems, especially in Islamic law. Many new problems are previously those whose provisions have not been regulated in nash. Then the scholars initiated a practical method to analyze a phenomenon related to Islamic law. The emergence of maqashid shari'ah became a phenomenal thought that contributed a lot to the scientific treasures of Islamic Law, and made Islamic law itself easy to apply in the era of now to respond to all sorts of new things. In this case, the author will bring up the existence of maqashid shari'ah as an approach in Islamic law. This research method is a qualitative method with a type of literature (library research). This research is descriptive, namely containing data and then analyzing and then drawing conclusions. The data contained in this study is maqashid shari'ah. The result of this study is that maqashid shari'ah in the study contributes in the form of: a). Giving birth to new theories; b). As a method of approach in Islamic law; c). In the scientific discipline, maqashid shari'ah becomes part of the Philosophy of Islamic Law, which is about the nature of the derivation of Islamic law or shari'a itself.